Penegakan Hukum Tindak Pidana Pencurian Dengan Kekerasan di Wilayah Hukum Polsek Pangkalan Berandan - Dediyansyah Putra Ginting; Taufik Siregar; Wessy Trisna (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is to find out and analyze law enforcement and the obstacles that occur in the criminal act of theft with violence in positive law in the Pangkalan Berandan Police Legal Area. The research method used is normative law and empirical law (combined). The results of the study found that the crime of theft with violence in positive law. Law enforcement against the crime of theft with violence The Pangkalan Brandan Sector Police submit cases of theft with violence against vehicles that occur to law enforcement agencies to be processed in accordance with applicable legal provisions, where penalties or criminal sanctions imposed on perpetrators are expected to provide a deterrent effect to perpetrators in accordance with sentencing purposes. The obstacle factor in law enforcement in the crime of theft through violence is the victim dies, the perpetrator is a minor, the suspect easily escapes, and the perpetrator eliminates evidence.